ILRI on a disc : (International Livestock Research Institute, 1998)
This CD-ROM contains a virtual library of over 500 publications produced by the International Livestock Research Institute (ILRI), the International Laboratory for Research on Animal Diseases (ILRAD) and the International Livestock Centre for Africa (ILCA).